Pengaruh Pelatihan, Jiwa Korsa Dan Kerja Tim Terhadap Kinerja Prajurit Berbasis Teknologi Informasi - Marsono (Faculty of Social Science, Universitas Negeri Malang, 2019)
Special Forces of the Indonesian Air Force, is a force that has special advantages. The 'more special force' was called the Bravo 90 Unit, whose members consisted of a number of selected Paskhas personnel. The performance of this unit is very much needed in the context of completing tasks to support the main tasks of the Air Force. The purpose of this research is to look at performances that can be influenced by various variables including the training variables, the soul of the body and teamwork. Research using quantitative methods and path analysis techniques with survey design. The development of information technology can be used as a supporting device in achieving the desired performance. The results showed there was a positive direct effect of training on soldier performance, esprit de corps on soldier performance, teamwork on soldier performance, training on teamwork, esprit de corps on teamwork, and teamwork on esprit de corps. So that the variables that can affect the performance need to be fostered continuously cohesiveness in order to improve the performance of information technology-based soldiers.